Factors, Phonology, Morphology, Syntax, And Semantics of Second Language Acquisition in Students' Kindergarten (TK) Pontianak - Sunarni Sunarni (Budapest International Research and Critics University, 2022)
Children's language development starting from birth to the age of three years, in particular, has acquired thousands of vocabularies, phonological and grammatical systems and the same complex rules for using their language properly in many social settings. Based on this statement, this study aims to analyze the acquisition of a second language, specifically Indonesian for children 4-6 years old at the Pontianak Sisters Kindergarten, West Kalimantan in the school environment at the phonological, morphology, syntax and semantic levels. The centre of this research is the acquisition of Indonesian in children aged 4-6 years at the Pontianak Sisters Kindergarten, West Kalimantan, at the level of phonology, morphology and syntax as well as semantics in the school environment. The research method is qualitative descriptive with a descriptive analysis model. The results showed that: (1) There were still children aged 4- and 5-years experiencing changes in the sound /r/ pronounced /l/, /s/ pronounced /c/ and sounds, while children aged six years had already obtained all vowel sounds and consonant sound, there is no change in the sound /r/ which changes /l/. (2) Children aged four years in obtaining morphology have not yet obtained words that have received affixation. Incomplete morphemes appear while children aged five years have appeared with intact morphemes and prefixes meN- and at the age of 6 years, there are more affixation acquisitions. (3) At the syntactic level, children aged four years only get two-word utterances, while children aged 5-6 years have obtained speeches of several words (4) At the semantic level almost all children's utterances contain denotative meanings, there are also sentences that appear with connotative meaning.